Zeranol Residue Detected by HPLC in Bovine Meat from Three Different Cities in Java Island - R. Widiastuti; Y. Anastasia (Tropical Animal Science Journal, 2020)
Zeranol is one of non-steroidal hormonal growth promoters (HGP) that is still permitted to be used in some countries such as Australia, the United States, and others to increase weight gain. However, this non-steroidal HGP is not permitted in Indonesia. The use of zeranol to increase the growth of livestock can cause the occurrence of residue in livestock tissues and organs, having a great dangerous potential for human health. This study aimed to investigate the presence of zeranol residues in 105 samples of bovine meat collected from Jakarta, Surabaya, and Malang cities and analyzed by high-performance liquid chromatography (HPLC). The samples were added with the deproteinizing extractant of 0.2% metaphosphoric acid and acetonitrile (6:4, v/v), and purified using SAX SPE cartridge. Zeranol was then analyzed by HPLC using Shimp-pack VP-ODS (4.6x250 mm) column with a mixture of acetonitrile-water (40:60, v/v) as the mobile phase and detected on photo diode array detector at 262 nm. The recoveries of the method of 3 different concentrations (2, 5, and 10 ng/g) of zeranol were 73.96% to 103.48%. The detection limit and quantification limits were 0.54 ng/g and 1.80 ng/g, respectively. Zeranol residues were detected in 12 (11.43%) out of 105 samples at the concentration of 1.67 to 33.29 ng/g and 7 among them exceeding 2.0 ng/g. The results obtained in this study indicated that zeranol was still being used to increase cattle-meat production. Therefore, strict control must be implemented at all stages, from production to consumption, regarding the application of this HGP in livestock.